Comparative Analysis of Six Lagerstroemia Complete Chloroplast Genomes - Xu, Chao; Dong, Wenpan; Li, Wenqing; Lu, Yizeng; Xie, Xiaoman; Jin, Xiaobai; Shi, Jipu; He, Kaihong; Suo, Zhili (Frontiers in Plant Science, 2017)
Crape myrtles are economically important tree species of the genus Lagerstroemia L. (Lythraceae), with a distribution from tropical to northern temperate zones. They are positioned phylogenetically to a large subclade of rosids (in the eudicots) which contain more than 25% of all the angiosperms. Lagerstroemia plants are important ornamental trees which produce big and showy panicles of gorgeous flowers. They commonly bloom from summer till fall and are of significant value in of city landscape and environmental protection. Morphological traits are shared inter-specifically among plants of Lagerstroemia to certain extent and are also influenced by environmental conditions and different developmental stages. Thus, classification of plants in Lagerstroemia at species and cultivar levels is still a challenging task. Chloroplast (cp) genome sequences have been proven to be an informative and valuable source of cp DNA markers for genetic diversity evaluation. In this study, the complete cp genomes of three Lagerstroemia species were newly sequenced, and three other published cp genome sequences of Lagerstroemia were retrieved for comparative analyses in order to obtain an upgraded understanding of the application value of genetic information from the cp genomes. The six cp genomes ranged from 152,049 bp (L. subcostata) to 152,526 bp (L. speciosa) in length. Their organization, gene order and GC content, were similar to the typical cp genome structure of other higher plants. We analyzed nucleotide substitutions, insertions/deletions, and simple sequence repeats in the cp genomes, and discovered 12 relatively highly variable regions that will potentially provide plastid markers for further taxonomic, phylogenetic and population genetics studies in Lagerstroemia. The phylogenetic relationships of the Lagerstroemia taxa inferred from the cp genomes obtained high support, indicating that cp genome data may be useful in resolving relationships in this genus.